Risk Factors for Microvascular Complications of Diabetes in a High-Risk Middle East Population - Sohaila Cheema; Patrick Maisonneuve; Mahmoud Zirie; Amin Jayyousi; Hekmat Alrouh; Amit Abraham; Sura Al-Samraye; Ziyad Mahfoud; Ibrahim Mohammed Al-Janahi; Buthaina Ibrahim; Albert B. Lowenfels; Ravinder Mamtani (Journal of Diabetes Research)
Aims. Much of the diabetes burden is caused by its complications. This cross-sectional study aimed to determine the prevalence and risk factors for diabetic microvascular complications (retinopathy, nephropathy, and neuropathy) in a high-risk population. Methods. We collected information via a structured questionnaire and directly from the patient’s record on 1034 adult type 2 diabetic patients who were attending outpatient clinics in Qatar. Results. The mean age of the patients was 55 ± 10 years, and the mean duration of diabetes was 12.4 ± 8.9 years. Forty-five percent had one or more microvascular complications. Shared risk factors for multiplicity and for individual complications included family history, severity and duration of diabetes, and hypertension, but some risk factors were specific for individual microvascular complications. Early age at onset of diabetes was strongly associated with multiplicity of complications (P=0.0003). Conclusions. About half the diabetics in this high-risk population had one or more microvascular complications. Several well-established risk factors were associated with multiplicity and individual microvascular complications, but each separate microvascular complication was linked to a somewhat different constellation of risk factors.